2022
DOI: 10.3390/ijerph192417000
|View full text |Cite
|
Sign up to set email alerts
|

Iron Deficiency and Deranged Myocardial Energetics in Heart Failure

Abstract: Among different pathomechanisms involved in the development of heart failure, adverse metabolic myocardial remodeling closely related to ineffective energy production, constitutes the fundamental feature of the disease and translates into further progression of both cardiac dysfunction and maladaptations occurring within other organs. Being the component of key enzymatic machineries, iron plays a vital role in energy generation and utilization, hence the interest in whether, by correcting systemic and/or cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 121 publications
0
4
0
Order By: Relevance
“…[14,53] To date, many studies have investigated whether intravenous iron therapy effectively reverses myocardial remodeling and prevents myocardial remodeling owing to ischemic or non-ischemic injury, which is of great interest. [54,55] However, studies on the relationship between circulating iron parameters and myocardial iron are limited, and findings vary between studies; thus, the significance of circulating iron parameters as representatives of myocardial iron content remains unclear. [54,56] Although the relationship between the two is unclear, different studies have shown that ID, defined using circulating iron parameters, aids in diagnosing patients with HF and ID.…”
Section: Discussionmentioning
confidence: 99%
“…[14,53] To date, many studies have investigated whether intravenous iron therapy effectively reverses myocardial remodeling and prevents myocardial remodeling owing to ischemic or non-ischemic injury, which is of great interest. [54,55] However, studies on the relationship between circulating iron parameters and myocardial iron are limited, and findings vary between studies; thus, the significance of circulating iron parameters as representatives of myocardial iron content remains unclear. [54,56] Although the relationship between the two is unclear, different studies have shown that ID, defined using circulating iron parameters, aids in diagnosing patients with HF and ID.…”
Section: Discussionmentioning
confidence: 99%
“…More than 95% of ATP in the heart is produced by mitochondrial oxidative phosphorylation, and less than 5% of ATP is produced by glycolysis. 41 Any minor changes in ATP production and metabolism in myocardial tissues will affect the normal function of the heart. Mitochondria are the centre of myocardial energy metabolism, and their structural integrity and normal function are the basis for normal cardiac electrophysiological activity.…”
Section: Discussionmentioning
confidence: 99%
“…Myocardial energy metabolism disorder is caused by an imbalance of ATP generation or decomposition in the heart. More than 95% of ATP in the heart is produced by mitochondrial oxidative phosphorylation, and less than 5% of ATP is produced by glycolysis 41 . Any minor changes in ATP production and metabolism in myocardial tissues will affect the normal function of the heart.…”
Section: Discussionmentioning
confidence: 99%
“…Improving the functioning of the bone marrow and the erythroid line cannot be a key element, as iron works across a wide spectrum of Hb and red cell indices, and even in patients without anemia [ 25 , 37 ]. Effects on myocardial energetics are difficult to prove, although we have some limited mechanistic data on improving skeletal muscle energetics [ 38 ••], as well as a few proof-of-concept experiments in rodents and cell lines reviewed in detail elsewhere, demonstrating that abnormal cardiomyocyte energetics due to induced less or more severe ID (and also consequent anemia) can be reversed through the rapid replenishment of the missing iron [ 39 , 40 ]. It remains also unknown why, for example, in non-ischemic HF FCM does not impact “hard” clinical outcomes as it does in patients with primary ischemic etiology of the disease, as demonstrated in one of the sub-analyses of the AFFIRM-AHF trial [ 41 ].…”
Section: Iron Deficiency and The Heart—uncertainties Regarding Defini...mentioning
confidence: 99%